Taxing you is tiring me out: Emotional labor and job performance among local revenue collectors in Thailand - Chuayprakong, Pawinee (Journal of Contemporary Social Sciences and Humanities, 2025)
In a cash-based economy, local governments depend on local tax collectors non-professional employees who wander in neighborhoods to collect cash as tax payments from local residents. Their encounters, nonetheless, may not always go smoothly. Despite being mentally exhausted, local tax collectors must effectively exert emotional labor the management of feelings to create preferred facial and bodily display to maximize local revenue. Most studies on emotional labor focus on professional occupations in developed countries. Hence, through a process-tracing method, this study qualitatively inquires the causal sequence of emotional labor and job performance of local revenue collectors in Thailand. Fifteen in-depth interviews were conducted and a constant comparative method was applied to analyze the interview data. The results offer a preliminary causal process of emotional labor and job performance, underscoring the existence and the relationship between emotional labor on performance. Particularly, general tax knowledge among the residents and revenue collectors’ local knowledge can simmer down the intense encounters and lower the levels of emotional labor. In the case of surface acting, the revenue collectors can seek support and professional advice from the online network of the local revenue administration to surpass those intense encounters without jeopardizing the revenue-generating performance. Meanwhile, the revenue collectors’ local knowledge leads them to perform deep acting and provide tax education to the local residents, which eventually boosts their willingness to pay local taxes. This study recommends that local policymakers include emotional labor training into their organizations’ performance improvement platforms. It also discusses methodological limitations and future research directions.